2017
DOI: 10.1016/j.celrep.2017.06.084
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Genetic Variation in ERAP1 Aminopeptidase that Prevents Human Cytomegalovirus miR-UL112-5p-Mediated Immunoevasion

Abstract: Herein, we demonstrate that HCMV miR-UL112-5p targets ERAP1, thereby inhibiting the processing and presentation of the HCMV pp65 peptide to specific CTLs. In addition, we show that the rs17481334 G variant, naturally occurring in the ERAP1 3' UTR, preserves ERAP1 from miR-UL112-5p-mediated degradation. Specifically, HCMV miR-UL112-5p binds the 3' UTR of ERAP1 A variant, but not the 3' UTR of ERAP1 G variant, and, accordingly, ERAP1 expression is reduced both at RNA and protein levels only in human fibroblasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…However, the HCMV gene expression pro le has not been explored in CRC tissue, which was evaluated by next-generation sequencing in this study. A total of 119 HCMV genes were detected in CRC tissues; 18 HCMV viral genes were detected in patients with SLE [33], among which 17 were detected except for UL112, which was subsequently found to function in immunomodulation [34]. We found that these HCMV genes which were correlated with DNA replication, gene expression regulation, and immunity showed high reads in CRC tissues.…”
Section: Discussionmentioning
confidence: 80%
“…However, the HCMV gene expression pro le has not been explored in CRC tissue, which was evaluated by next-generation sequencing in this study. A total of 119 HCMV genes were detected in CRC tissues; 18 HCMV viral genes were detected in patients with SLE [33], among which 17 were detected except for UL112, which was subsequently found to function in immunomodulation [34]. We found that these HCMV genes which were correlated with DNA replication, gene expression regulation, and immunity showed high reads in CRC tissues.…”
Section: Discussionmentioning
confidence: 80%
“…Consistently, ERAP1 expression was significantly decreased by miR-UL112-5p overexpression only in fibroblasts from AA individuals, while fibroblasts from GG individuals did not show any alteration in RNA and protein levels [73]. Even more important, a significantly reduced HCMV seropositivity was detected among GG individuals suffering from multiple sclerosis, a disease model in which HCMV infection is negatively associated with adult-onset disorder [73].…”
Section: Eraps and Human Cytomegalovirus (Hcmv)mentioning
confidence: 88%
“…A more recent study focused onto another HCMV miRNA, miR-UL112-5p, whose function resembles the one played by miR-US4-1. Indeed, miR-UL112-5p directly targets the 3' UTR of ERAP1-A SNP variant, thus downregulating its mRNA expression and altering the presentation of many HCMV-derived antigenic peptides to CD8 + T cells [73]. Notably, the authors identified the rs17481334-G SNP variant, naturally occurring in the ERAP1 3' UTR, which disrupts the consensus sequence for HCMV miR-UL112-5p and, in turn, prevents ERAP1 targeting and degradation [73].…”
Section: Eraps and Human Cytomegalovirus (Hcmv)mentioning
confidence: 99%
See 2 more Smart Citations